(untitled) (International Journal of Engineering and Computer Science, 2017)
Eye tracking is the process of watching where a person is looking. The significance of eye movements with regards to the perception of and attention to the visual world is certainly acknowledged since it is the means by which the information needed to identify the characteristics of the visual world is gathered for processing in the human brain. Hence, robust eye detection and tracking are considered to play a crucial role in the development of Human-Computer Interaction (HCI), creating attentive user interfaces and analyzing human affective states. The proposed work uses ANN-based head movement detection with eye tracking. This proposed system aim to estimate the head movements and to locate the eye in the image and then use the obtained information about the eye region and the head pose to estimate the eye gaze direction to be used in various applications, such as HCI, virtual reality, driver assistance systems and assistance for people with disabilities